DEVELOPING ENGLISH LEARNING MATERIAL FOR SPEAKING SKILL BASED ON PROBLEM -BASED LEARNING (PBL) AT FIRST SEMESTER OF THE EIGHTH GRADE OF JUNIOR HIGH SCHOOL - Hidha Fajarwati; Amirudin Latif (Premise: Journal of English Education and Applied Linguistics, 2014)
The objective of the study is to develop practical English speaking materials by using Problem Based Learning (PBL). The design of the study is research and development which attempts to develop descriptive and recount text for speaking materials. The steps of the research and development for the materials include self evaluation, expert review, one-to-one try out, small group try out, field test, and final product. The subjects of this research are the eighth grade students of State Junior High School 6 Metro. The result of the study is English learning material for speaking skill based on problem based learning.